Aktivitas Antipiretik Ekstrak Etil Asetat Daun Seligi (Phyllanthus buxifolius Muell.Arg) Pada Mencit Jantan Galur Swiss - Siwi Hastuti; Susi Endrawati (Jurnal Biologi Papua, 2016)
Seligi (Phyllanthus buxifolius Muell. Arg) empirically proven to reduce pain and swelling in joints. The research of analgesic activity and antiinflammatory of seligi leaves was done, however antipyretic research not be found. The aim of this research was to examine the effect of ethyl acetate extract from seligi leaves as antipyretic on white male mice strain Swiss induced with DTP-HB-Hib vaccine. Ethyl acetate extract of seligi leaves doses of 100, 200 and 400 mg/kg showed antipyretic effect with values of 18.77 ± 1.99, 24.81 ± 4.34 and 35.39 ± 2.84 % respectively whereas paracetamol dose of 91 mg/kg have antipyretic effect with value of 50.38 ± 6.90 %. One way ANOVA test showed no significant difference for p (0.001) <p (0.05). Significance LSD Post hoc test for paracetamol 91 mg/kg with all seligi extract and extract seligi dose of 400 mg/kg with seligi extract 100 mg/kg have significant difference. While seligi extract 400 mg/kg with seligi extract 200 mg/kg and extract seligi 200 mg/kg with seligi extract 100 mg/kg no significant difference. Ethyl acetate extract of seligi leaves can be developed as source for active compounds with antipyretic activity.Key words: antipyretic, seligi, Phyllanthus buxifolius, temperature, mice.